Percutaneous cholecystostomy without interval cholecystectomy as definitive treatment of acute cholecystitis in elderly and critically ill patients. - Griniatsos, John; Petrou, Athanasios; Pappas, Paris; Revenas, Konstantinos; Karavokyros, Ioannis; Michail, Othon P; Tsigris, Christos; Giannopoulos, Athanasios; Felekouras, Evangelos (South Med J, 2008)
OBJECTIVE: The aim of this study was to evaluate the safety and effectiveness of percutaneous cholecystostomy without interval cholecystectomy as definitive treatment for acute cholecystitis in elderly or critically ill patients with various coexisting diseases who were unfit for surgery under general anesthesia. DESIGN: Between July 2004 and June 2006, 24 consecutive elderly and critically ill patients unfit for surgery, suffering from acute cholecystitis, and in whom significant comorbid factors were present, underwent percutaneous cholecystostomy as an emergency procedure at Laiko General Hospital. The diagnosis and the severity of acute cholecystitis were based on the Tokyo Guidelines, whereas the American Society of Anesthesiologists' (ASA) physical status classification was used for the perioperative risk stratification for cholecystectomy. RESULTS: There were 14 male and 10 female patients with a median age of 79 years. Acute cholecystitis was classified as grade 2 in 20 patients and as grade 3 in 4 patients; 17 patients were classified as ASA score III and 7 as ASA score IV, whereas a total of 52 comorbid factors were present. Gallstones were disclosed as the underlying etiology in 23 patients, whereas one patient was diagnosed as suffering from acalculous cholecystitis. Percutaneous cholecystostomy was technically feasible in all patients (100%). Clinical improvement was noticed in 14 patients within 24 hours and in all patients within 72 hours. Statistically significant reduction in the values of white blood cells, C-reactive protein, and axillary body temperature were observed within 72 hours. The procedure-related mortality was 4%, whereas within a median follow-up of 17.5 months, definitive and effective control of symptoms was achieved in 90.5% of the patients. CONCLUSIONS: For the subgroup of extremely high-risk and unfit for surgery patients, percutaneous cholecystostomy might be considered as the definitive treatment since it controls the local symptoms and the systemic inflammatory response.
Keywords: Acute Disease; Aged; Aged, 80 and over; Cholecystectomy; Cholecystitis; Cholecystostomy; Comorbidity; Critical Care; Female; Humans; Male; Minimally Invasive Surgical Procedures; Postoperative Complications; Recurrence; Reoperation; Retrospective Studies; Risk Factors; Survival Rate